Rethinking the farmer's role in plant breeding : local bean experts and on-station selection in Rwanda - Sperling, L.; Loevinsohn, ME; Ntabomvuras, B (Cambridge University Press, 1993)
Varietal selection is particularly difficult for very heterogeneous environments where farmers have a range of preferences. To address these issues in Rwanda, local bean experts, generally women, are invited to the research station to assess cultivars and to select those they prefer for their plots. Farmers use observed yield as only one of several criteria to predict varietal performance in their more stressed home environments. The varieties they choose are often higher yielding on-farm and are retained longer by farmers than those selected by the breeders. The results of early farmer involvement also compare favourably with those of the standard breeding programme in terms of enhanced genetic diversity and reduced research costs. There are few pre-conditions for developing such a client-driven breeding programme.